PROPHETIC LEADERSHIP AND GLOBAL CITIZENSHIP EDUCATION: A THEMATIC INTERPRETATION OF MOSES NARRATIVE IN TAFSIR AL-AZHAR FOR CONTEMPORARY CHARACTER DEVELOPMENT - Hernawati Hernawati; Andy Hadiyanto; Selvi Syafitri (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
This research aims to find the values in the story of the Prophet Moses and relate them to the concept of GCED and character education in the 21st century. This research is qualitative research that analyzes the story of the Prophet Moses in Tafsir Al-Azhar by Buya Hamka. The research method used is thematic interpretation with content analysis and source triangulation to ensure the validity of the data. Primary data includes verses of the Qur'an and Tafsir Al-Azhar, while secondary data includes academic literature related to GCED, 21st century character education, and another relevant research. The results of the study show that the story of the Prophet Moses in Tafsir Al-Azhar displays the integration of prophetic leadership values, character education, and universal humanitarian principles that are in harmony with 21st century competence. These values include the cognitive domain (rational and reflective thinking in decision-making), the socio-emotional domain (empathy, self-awareness, and emotional control), and the behavioral domain (real action in upholding justice and humanity). The integration of the interpretation of the Qur'an with the GCED framework shows that Islamic education is not only oriented to the transfer of knowledge, but also to the formation of a global character that is ethical, adaptive, and caring for humanity. The story of the Prophet Moses is relevant as the foundation for developing 21st century skills such as critical thinking, collaboration, communication, and adaptability. This research provides a conceptual and practical foundation for the development of a curriculum and learning strategies based on Islamic values that can connect character education with global and contextual learning.